Association of thrombocytopenia with in-hospital outcome in patients with acute ST-segment elevated myocardial infarction. (3rd October 2019) - Liu, Ru; Liu, Jia; Yang, Jingang; Gao, Zhan; Zhao, Xueyan; Chen, Jue; Qiao, Shubin; Gao, Runlin; Wang, Qingsheng; Yang, Hongmei; Wang, Zhifang; Su, Shuhong; et al.
Abstract: This study investigated the association of thrombocytopenia (TP) with in-hospital medication and outcome of patients with acute ST-segment elevated myocardial infarction (STEMI). A total of 16, 678 consecutive patients with STEMI from multiple centers that participated in the China Acute Myocardial Infarction registry was included. In-hospital adverse event rates were compared between patients with TP and those with a normal platelet count. Multivariate logistic regression was applied to adjust for confounders. Propensity score matching (PSM) was applied to control for baseline differences. There were 359 patients with baseline TP, accounting for 2.2% of the total cohort. The risk of in-hospital death (11.1% vs 6.0%, P < 0.001); major adverse cardiovascular events (MACE) (11.7% vs 6.4%, P < 0.001); and newly occurred or aggravated heart failure, cardiogenic shock, malignant arrhythmia, acute pulmonary embolism, and bleeding (3.6% vs 1.8%, P = 0.024) were significantly higher in the TP group than in the normal platelet group. After multivariate adjustment, TP was independently associated only with malignant arrhythmia (odds ratio: 1.49; 95% confidence interval: 1.09–2.05, P = 0.014). A total of 289 patients in each group were matched by PSM. The risk of all endpoints was not significantly different between the two matched groups before and after multivariate adjustment. In-hospital outcomes were worse in patients with STEMI and TP than in those with a normal platelet count. However, baseline TP was not independently associated with in-hospital death, MACE, or bleeding risk after multivariate adjustment and controlling for baseline differences.